Internet Usage and Economic Growth: The Case of Mexico - Yu Hsing; Yun-Chen Morgan; Antoinette S. Phillips; Carl Phillips (Quantitative Economics and Management Studies, 2020)
This paper finds that more internet users as a percentage of total population promote economic growth in Mexico and that the impact exhibited a nonlinear relation and was greater in the initial stage of Internet adoption. In addition, less government budget deficit as a percent of GDP, a higher real stock price, real peso appreciation, a higher real crude oil price or a lower expected inflation rate would enhance economic growth.